Pengajian Alam Melayu di pentas global: Teknologi maklumat dan penstrukturan ilmu di ATMA, UKM - Shamsul A. B.,; Rumaizah Mohamed,; Haslindawati Hamzah, (Universiti Kebangsaan Malaysia, 2004)
This paper traces the knowledge ‘restructuration’ exercise that has been carried out at the Institute of the Malay World and Civilization (ATMA), Universiti Kebangsaan Malaysia, since April 1999. It has changed ATMA’s academic orientation and it includes the introduction and active use of Information and Communications Technology (ICT). It also describes the evolution of the construction of a series of digital databases relating to Malay World Studies, the one and only on-line Malay World Studies database available in the world today that has more than 22,000 single-text articles on various aspects of the Malay world written in a number of languages gathered from a number of resources. Besides, ATMA has also built a number of other digital databases, including on pantun and peribahasa, all of which could be reached at URL www.atma.ukm.my. The underpinning concept of and the motivation that has propelled the project shall be described too including the technical aspect. The challenges that ATMA has to confront in the whole effort shall be outlined, and the possible one on our way to reach the 50,000 single-text articles target. The next stage of the project is create a home for all ATMA’s existing and future digital databases, that is, a portal and it shall be called www.malaycivilization.com. The initial effort of the said task has been funded by the DAGS Grant Scheme made available by the National IT Council of Malaysia